The impact of Digital Leadership Competencies on Virtual Team Effectiveness in MNC companies in Penang, Malaysia - Cheng Soon, Chee; Salamzadeh, Yashar (Journal of Entrepreneurship, Business and Economics; Vol 8 No 2 (2020), 2021)
This research objective is to examine the impact of Digital Leadership competencies on Virtual Team Effectiveness in MNC companies in Penang, Malaysia. The survey was conducted among 150 respondents who are working in MNC companies in Penang, with experience in a virtual team. The diversified range of respondents was chosen to predict the impact of digital leadership competencies on virtual team effectiveness. Data collected was analysed using SmartPLS. Hypotheses were tested based on the structural equation model. The results come out with 2 variables (E-Communication Competency & E-Trust Competency) having a positive & significant relationship with virtual team effectiveness. The remaining four variables, namely E-Social Competency, E-Team Competency & E-Change Competency, found to be no significant relationship towards virtual team effectiveness. Firstly, MNC companies size varies; as such, the study may be slightly biased. As more virtual teams are available to sample this analysis from large MNC companies, the outcome will appear to lean towards them. Secondly, due to the data collection limitation, virtual teams are represented by only one respondent per team in this study. As such, it may represent some bias if the response being used to represent the team. Results of this research can be used as guidance for organization Leaders in managing virtual teams more effectively. The E-Communication competency & E-Trust Competency can be applied and eventually enhance virtual team efficiency. This analysis will benefit future researchers or leaders of organizations to call attention to variables that contribute to virtual teams' effectiveness. This study is to investigate factors that have a positive influence on virtual team effectiveness. Digital Leadership Competency is chosen as independent variables that potentially have a great impact on virtual team effectiveness. As part of measuring Virtual Team effectiveness, Media Richness Theory is taken into consideration to underpin this study. Research paper Keywords: Virtual teams; Digital leadership competencies; PLS-SEM; Malaysia; Virtual teams’ effectiveness Reference to this paper should be made as follows: Cheng Soon, C., & Salamzadeh, Y. (2020). The impact of Digital Leadership Competencies on Virtual Team Effectiveness in MNC companies in Penang, Malaysia, Journal of Entrepreneurship, Business and Economics , 8 (2), 219–253.